ANALISIS SKENARIO KEMITRAAN KEHUTANAN ANTARA GAPOKTAN RIDING BERSATU DAN PT. BUMI MEKAR HIJAU (Suatu Kasus di Desa Riding Kecamatan Lampam Kabupaten Ogan Komiring Ilir, Provinsi Sumatera Selatan) - Purnawan, Handoyo Wahyu; Thayib, Hasroel; Abdini, Chairil (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Society and PT. BMH has an agreement on peat areas. Until now, forestry partnerships is not implemented. As lesson learning, scenario analysis analyzes driving factors, critical uncertainty driving factors, and composing a possible scenario in 2022. Critical uncertainty driving factor is the adaptive culture and policy alignment. Solution to solving environmental problems must position humans at the beginning, "Put People First", namely stakeholders. The integration of the policies and adaptive culture in the gold peat scenario does not lead to a succesed forestry partnership. Partnerships can work if the company replaces raw materials peat friendly.